Are patients willing to accept longer travel times to decrease their risk associated with surgical procedures? A systematic review - Stefanie Bühn; Jakob Holstiege; Dawid Pieper (BMC, 2020)
Abstract Background Distance to a hospital is an influencing factor for patients´ decision making when choosing a hospital for surgery. It is unclear whether patients prefer to travel further to regional instead of local hospitals if the risk associated with elective surgery is lower in the farther hospital. The aim of our systematic review was to investigate patient preferences for the location of care, taking into consideration surgical outcomes and hospital distance. Methods MEDLINE (PubMed), EconLit, PsycInfo and EMBASE were searched until November 2019. We included experimental choice studies in which participants were asked to make a hypothetical decision where to go for elective surgery when surgical risk and/or distance to the hospitals vary. There was no restriction on the type of intervention or study. Reviewers independently extracted data using a standardized form. The number and proportion of participants willing to accept additional risk to obtain surgery in the local hospital was recorded. We also extracted factors associated with the decision. Results Five studies exploring participants´ preferences for local care were included. In all studies, there were participants who, independently of a decreased mortality risk or a higher survival benefit in the regional hospital, adhered to the local hospital. The majority of the patients were willing to travel longer to lower their surgical risk. Older age and fewer years of formal education were associated with a higher risk tolerance in the local hospital. Conclusions Whether patients were willing to travel for a lower surgery-associated risk could not be answered in a straightforward manner. The studies we identified showed that decision making also relies on factors other than on rational information on risk or distance to hospital. Trial registration International prospective register of ongoing systematic reviews (PROSPERO): CRD42016033655. Registered 1 January 2016.